(untitled) (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
The performance of the Baris Putus Dance as a sacred dance acts as an accompaniment to the Pitra Yajña ceremony in Sinabun Village. To increase the sacredness of the performance, philosophical studies are an important foundation for the sustainability and also increase the sacredness of the Baris Putus Dance in its performance at the Pitra Yajña ceremony. Based on this background, in this study there are three problems that will be discussed, including; (1) What is the basis for the sustainability of the Baris Putus Dance at the Pitra Yajña ceremony in Sinabun Village, (2) What is the form and function of the Baris Putus Dance at the Pitra Yajña ceremony in Sinabun Village, (3) What is the philosophical meaning contained in the Baris Putus Dance at the Pitra Yajña ceremony in Sinabun Village. The theories used in analyzing the formulation of the problem are (1) Koentjaraningrat’s religious theory, (2) Talcott Parsons’ Structural Functional Theory, (3) Pierce’s Semiotic Theory. The methods used to collect data are: observation, interviews, documentation and literature studies. The collected data were analyzed using qualitative descriptive analysis methods with steps of data reduction, data presentation, and drawing conclusions. The results of the research and data analysis show that: (1) The basis for the sustainability of the Baris Putus Dance in the Pitra Yajña ceremony is seen from the perspective of the Pitra Yajña ceremony, the role of religion and religious awareness, and the role of the community and the Village Government. (2) The form and function of the Baris Putus Dance seen from its form consists of movement and choreography, costumes, and the performance process. then the performance function consists of religious functions, social functions, and preservation functions. (3) The philosophical meaning of the Baris Putus Dance in the Pitra Yajña ceremony, seen from the meaning of the costume, harmony, and karmapala.